Administration of eicosapentaenoic acid may alter high-density lipoprotein heterogeneity in statin-treated patients with stable coronary artery disease: A 6-month randomized trial. Issue 3 (March 2020) - Tani, Shigemasa; Matsuo, Rei; Yagi, Tsukasa; Matsumoto, Naoya
Highlights: We hypothesized that eicosapentaenoic acid (EPA) added to statin may alter high-density lipoprotein (HDL) heterogeneity. Additional EPA therapy decreased the HDL3 level and increased the HDL2/HDL3 ratio. The increase in EPA/arachidonic acid (AA) ratio may be a predictor of elevation of the HDL2/HDL3 ratio. EPA/AA ratio may be a useful marker for facilitating reverse cholesterol transport. Combination therapy of statin and EPA may be a potential treatment option in coronary artery disease. Abstract: Background: Combined statin plus eicosapentaenoic acid ( EPA) therapy might be a potentially effective treatment option to prevent coronary artery disease (CAD). The serum EPA/arachidonic acid (AA) ratio has been identified as a potential new risk marker for CAD. Few data exist whether administration of EPA could affect high-density lipoprotein (HDL) particle size. We hypothesized that the addition of EPA to ongoing statin therapy may result in altered HDL heterogeneity. Methods: We conducted this 6-month, single-center, prospective, randomized open-label clinical trial to investigate the effect of the additional administration of EPA on the HDL heterogeneity (HDL2, HDL3, and HDL2 /HDL3 ratio) in stable CAD patients receiving treatment with statins. We assigned stable CAD patients already receiving statin therapy to the EPA group (1800 mg/day: n = 50) or the control group (n = 50). Results: A significant decrease in the serum HDL3 level (−4.7% vs. −0.5%, p  = 0.037), but not of the serum HDL2 level, and a significant increase in the HDL2 /HDL3 ratio (5.5% vs. −5.1%, p  = 0.032) were observed in the EPA group as compared to the control group. Multiple regression analysis with adjustments for coronary risk factors identified the achieved EPA/ AA ratio as an independent and significant predictor of an increase of the HDL2 /HDL3 ratio (β = 0.295, p  = 0.001). Furthermore, the change in the serum cholesterol ester transfer protein mass was positively correlated with the change in the EPA/AA ratio in the EPA group (r = 0.286, p  = 0.044), but not in the control group (r = 0.121, p  = 0.401). Conclusion: Administration of EPA might decrease the serum HDL3 level, resulting in an increase in the HDL2 /HDL3 ratio. Furthermore, increased EPA/AA ratio by the addition of EPA to ongoing statin therapy might be an indicator of an increase in the HDL2 /HDL3 ratio, thereby regulating HDL particle size. Clinical Trial Registration: UMIN (http://www.umin.ac.jp/ ) Study ID: UMIN000010452